Penyelesaian Sengketa Ketenagakerjaan Terhadap Pekerja Atas Penahanan Ijazah Dalam Perjanjian Kerja Waktu Tertentu Di Dinas Tenaga Kerja Sumatera Utara - Wibowo, Fernanda; Syaputra, Muhammad Yusrizal Adi (ARBITER: Jurnal Ilmiah Magister Hukum, 2025)
This study aims to analyze the role of the North Sumatra Provincial Manpower Office in resolving disputes over the withholding of diplomas in employment relationships based on the Fixed-Time Work Agreement (PKWT), as well as examining the legal rights and obligations of the parties in resolving labor disputes based on Circular Letter Number M/5/HK.04.00/V/2025 concerning the Prohibition of Retention of Diplomas and/or Personal Documents Belonging to Workers/Laborers by Employers. This study uses a normative juridical method with a qualitative descriptive approach. Data was obtained through literature studies and interviews with the Manpower Office. The study's results indicate that detaining a diploma without a valid legal basis can be considered an unlawful act and is contrary to the principle of worker protection as stipulated in Law Number 13 of 2003 concerning Manpower and related laws and regulations. Additionally, the Manpower Office plays a crucial role in facilitating dispute resolution through mediation and protecting workers' rights. This research emphasizes the urgency of strengthening policies and law enforcement to prevent the practice of withholding diplomas that are detrimental to workers and maintain the balance of industrial relations.